Biotin immunoassay interference: A UK-based prevalence study. (January 2021) - Sanders, A; Gama, R; Ashby, H; Mohammed, P
Background: Biotin interference in biotin-streptavidin-based immunoassays is increasingly reported due to individuals taking biotin-containing supplements and patients prescribed biotin. The reported prevalence of serum biotin above the lowest threshold (≥10  µ g/L) for interference in Roche Diagnostics immunoassay tests is 0.8% in Australia and 7.4% in the USA. There are, however, no such data in UK populations. In a service evaluation, we therefore studied the prevalence of biotin interference in routine serum samples received in our laboratory. Methods: Biotin was measured in 524 anonymized surplus serum samples in which at least one immunoassay test had been requested. Results: The median (95% confidence intervals) for serum biotin was 0.27  µ g/L (0.07–0.93  µ g/L). Serum biotin was <10  µ g/L in all samples, <5 µ g/L in 522 (99.6%) and <1  µ g/L in 513 (98.1%) samples. In four samples, serum biotin was ≥2.5  µ g/L (0.8%). Conclusions: These data indicate that the probability of biotin immunoassay interference in our patient population is extremely low, with the exception of assays reporting the lowest interference thresholds (e.g. Ortho Troponin I assay [threshold ≥2.5  µ g/L]).